Meaningful outcomes for enhancing quality of life for individuals with autism spectrum disorder. Issue 1 (2nd January 2017) - Pfeiffer, Beth; Piller, Aimee; Giazzoni-Fialko, Tina; Chainani, Anjali
ABSTRACT : Background Autism spectrum disorder (ASD) is a developmental disorder that continues across the lifespan, but little research exists to examine interventions from both child and adult perspectives. The researchers in this study considered the perspectives of individuals with ASD and caregivers of children with ASD to determine interventions and outcomes perceived as meaningful for both children and adults. Methods Grounded theory methodology was used to guide data collection and analysis. Participants included 5 parents of children with ASD and 5 adults with ASD. Data were collected through interviews. Results A central theme of Intervention priorities for quality of life was supported . Individual themes identified from parents focused on future planning, community involvement, and scheduling and planning. Individual themes identified from the adults focused on misconceptions. Both groups shared the themes of acceptance; financial challenges; support, resources, and advocacy; skills learned; and socially and functionally based interventions. Conclusion Results support interventions and resources for individuals with ASD focused on meaningful outcomes, including acceptance, community involvement, social success, independent living, and vocational/financial stability.